2012
DOI: 10.1590/s1516-18462012005000023
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da qualidade de vida em indivíduos com paralisia facial periférica crônica adquirida

Abstract: OBJETIVO: analisar a qualidade de vida em indivíduos com paralisia facial periférica crônica adquirida. MÉTODO: foram selecionados, por meio de triagem, 12 indivíduos com paralisia facial periférica adquirida na fase de sequela, com etiologias de paralisia facial de Bell e Schwannoma após exérese. Foi verificado o grau da paralisia facial periférica adquirida de acordo com House & Brackmann9, além de ter sido realizada entrevista com perguntas fechadas, para verificar se havia interferência da paralisia fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…Amid the lack of objective evaluation tools and the difficulties in establishing a prognosis in the treatment of facial paralysis, quantification methods have emerged in order to clinically measure the facial movements 24 . The measurement Besides the stomatognathic functions, it was observed that patient 02 presented difficulty in opening and closing the mouth and pain in the TMJ region to chew and open the mouth just on the paralyzed side (left).…”
Section: Discussionmentioning
confidence: 99%
“…Amid the lack of objective evaluation tools and the difficulties in establishing a prognosis in the treatment of facial paralysis, quantification methods have emerged in order to clinically measure the facial movements 24 . The measurement Besides the stomatognathic functions, it was observed that patient 02 presented difficulty in opening and closing the mouth and pain in the TMJ region to chew and open the mouth just on the paralyzed side (left).…”
Section: Discussionmentioning
confidence: 99%
“…-Photographic documentation -Chevalier Scale 27 SANTOS & GUEDES (2011) 35 Study on the quality of life in subjects with acquired chronic peripheral facial palsy…”
Section: Scales Of the Degree Of Facial Paralysis: Analysis Of The Agreementmentioning
confidence: 99%
“…Calais et al (2005) 2 highlighted the importance of the participation of the speech therapist in the multidisciplinary team, who treats the patient with peripheral facial palsy, which also contributes with the most appropriate treatment to be offered to the patient, thus resulting in an improved quality of life. Santos and Guedes (2012) 15 concluded that the acquired chronic facial paralysis interfered with the quality of life of individuals in more serious degrees. In the study of Coulson et al (2004) 16 , aspects of emotional expression affected by facial paralysis with a significant reduction in social relationship were identified.…”
Section: Barros Et Al (2004)mentioning
confidence: 99%